2021
DOI: 10.3389/fmolb.2021.645823
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine, DNA Repair, and Genome Stability

Abstract: N6-methyladenosine (m6A) modification in mRNAs and non-coding RNAs is a newly identified epitranscriptomic mark. It provides a fine-tuning of gene expression to serve as a cellular response to endogenous and exogenous stimuli. m6A is involved in regulating genes in multiple cellular pathways and functions, including circadian rhythm, cell renewal, differentiation, neurogenesis, immunity, among others. Disruption of m6A regulation is associated with cancer, obesity, and immune diseases. Recent studies have show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 56 publications
0
13
0
Order By: Relevance
“…Zhang (2017) [34] suggested that this non-canonical DNA repair pathway works independently on phosphorylation of histone H2AX and is based on the formation of hybrid DNA-RNA loops. It was documented that such DNA-RNA structures appear in the genome as a consequence of DNA damage at transcription sites [35].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang (2017) [34] suggested that this non-canonical DNA repair pathway works independently on phosphorylation of histone H2AX and is based on the formation of hybrid DNA-RNA loops. It was documented that such DNA-RNA structures appear in the genome as a consequence of DNA damage at transcription sites [35].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, immunogenic biomarkers, LOH, HRD, TNB, ITH, and aneuploidy were also significantly negatively correlated with m6Ascore. The key role of m6A modification mediated regulators in modulating DNA repair and genome stability has gradually attracted attention (38). Some m6A methyltransferases can modify and regulate the levels of RNAs involved in DNA damage and repair, which in turn affect genomic instability (39).…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs also interact with m6A regulators to affect their function. It has been demonstrated that m6A RNA methylation plays important roles in a variety of biological processes, including cell differentiation, embryonic development, cell cycle regulation, circadian cycle, and stress responses ( 20 , 21 ). Growing evidence from in vivo and in vitro experiments and bioinformatic studies suggest that m6A RNA methylation regulators are closely related to the occurrence, developmental pathogenesis, progression and clinical prognosis of various cancers and cardiovascular diseases ( 22 , 23 ).…”
Section: Introductionmentioning
confidence: 99%